Fracture of humerus in a newborn during cesarean section: A case report - Meshram, Rajkumar M; Shinde, Sneha S; Mahajan, Shalaka V; Gholap, Siddhant; Nayak, Abinash D (Indian Journal of Case Reports, 2019)
Risk of birth injuries and long bone fractures are common in vaginal breech deliveries but have also occurred in the cesarean section. Here, we report the case of a term neonate who was admitted with swelling and paucity of movement of the right arm with a history of energetic traction during the emergency cesarean section. The diagnosis was confirmed by radiography and managed by plaster of paris slab. Obstetrician and pediatrician should remain vigilant regarding such rare complications so that these cases are not overlooked, as timely intervention and management are necessary to prevent disability and deformities in the future.